Practices employed by audiologists in the management of adult patients with multidrug-resistant tuberculosis in South Africa - M. Govender; J. Paken (South African Family Practice)
Introduction: Aminoglycosides used for treating multidrug-resistant (MDR) tuberculosis are ototoxic, leading to a need for audiological monitoring. While audiologists monitor ototoxicity, currently there are no guidelines on monitoring in the South African context. Therefore, the findings of this study might help to motivate the establishment of a more in-depth ototoxicity monitoring policy, which facilitates uniformity among audiologists managing patients with MDR tuberculosis. Therefore, the study aimed to describe the audiological practices employed by audiologists in the management of adult patients with MDR tuberculosis in South Africa.